Exergames for subthreshold depression among older adults - Li, Jinhui (2017)
The number and percentage of older adults continue to increase dramatically around the world. Subthreshold depression is not often highlighted in the field of gerontology, although it has a high prevalence rate among older adults. Subthreshold depression refers to a cluster of depressive symptoms in which the number, duration, or quality are insufficient to meet the diagnosis of a major depression. Among older adults, subthreshold depression is at least two to three times more prevalent than major depression and leads to many negative outcomes. Among the various depression treatments, which range from biological to psychosocial interventions, exercise is considered to be an effective and cost-efficient non-clinical intervention for subthreshold depression. Exergame is a special type of exercise, wherein the exercise activities are combined with video gaming. Several recent attempts to investigate the feasibility and preliminary effects of exergames as a depression intervention have been conducted. However, because of the lack of rigorous controlled studies in this domain, the true effectiveness of exergames on subthreshold depression remains unclear especially on older adults. Hence, it is important to investigate the anti-depressive effects of exergames and the potential influencing factors of using exergames as depression therapy for older adults with subthreshold depression.